Cardiac melanoma: Retrospective review of a rare disease at the Mayo clinic (1988–2015). (15th December 2017) - Tse, Chung Sang; Tan, Nicholas; Idossa, Dame; Click, Roger
Abstract: Background: Melanoma metastasizing to the heart (cardiac melanoma) is a rare entity that has been described only in autopsy studies or isolated pre-mortem case reports. We aim to better characterize cardiac melanoma, and describe its presenting features, imaging findings, and disease course with a case series collected over nearly 30 years. Methods: We performed a retrospective review of all patients diagnosed with cardiac melanoma at the Mayo Clinic from 1988 to 2015. Qualitative analysis was performed on patient demographics, clinical history, and imaging modalities. Results: 11 patients (7 male, median age 63 years) were identified with cardiac melanoma. Shortness of breath (64%) was the most common presenting symptom. Transthoracic echocardiography (TTE) was utilized in the assessment of all patients though it failed to identify 20% of masses that were seen on fluorodeoxyglucose positron emission tomography/computed tomography (FDG PET/CT) or cardiac magnetic resonance (CMR). The majority of masses were located within the cardiac chambers (46% right atrium, 18% right ventricle, 18% left atrium), and 36% appeared mobile on TTE. Patients lived for a median of 68 months (interquartile range [IQR] 14–143 months) after the initial diagnosis of primary melanoma, and only 12 months (IQR 2–150 months) after diagnosis of cardiac melanoma. Conclusion: Echocardiography can generally identify most cases of cardiac melanoma, though it misses one-fifth of masses seen on FDG PET/CT or CMR. Cardiac melanoma is associated with a poor prognosis.